(untitled) (Altre Modernità, 2019)
Roberta Mullini, Più del bronzo: Voci della poesia inglese della Grande Guerra (Günzburg, Oakmond Publishing, 2018, 123 pp. ISBN 978-3-96207-070-0, ISBN kindle: 978-3-96207-071-7) di Cristina Paravano